In vivo negative regulation of SARS-CoV-2 receptor, ACE2, by interferons and its genetic control - Ansari, A; Marchi, E; Ramamurthy, N; Aschenbrenner, D; Morgan, S; Hackstein, C-P; Lin, S-K; Bowden, R; Sharma, E; Pedergnana, V; Venkateswaran, S; Kugathasan, S; et al. (F1000 Research Ltd, 2021)
Background: Angiotensin I converting enzyme 2 (ACE2) is a receptor for the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) and differences in its expression may affect susceptibility to infection. Methods: We performed a genome-wide expression quantitative trait loci (eQTL) analysis using hepatitis C virus-infected liver tissue from 190 individuals. Results: We discovered that polymorphism in a type III interferon gene (IFNL4), which eliminates IFN-λ4 production, is associated with a two-fold increase in ACE2 RNA expression. Conversely, among genes negatively correlated with ACE2 expression, IFN-signalling pathways were highly enriched and ACE2 was downregulated after IFN-α treatment. Negative correlation was also found in the gastrointestinal tract where inflammation driven IFN-stimulated genes were negatively correlated with ACE2 expression and in lung tissue from a murine model of SARS-CoV-1 infection suggesting conserved regulation of ACE2 across tissue and species. Conclusions: We conclude that ACE2 is likely a negatively-regulated interferon-stimulated gene (ISG) and carriage of IFNL4 gene alleles which modulates ISGs expression in viral infection may play a role in SARS-CoV-2 pathogenesis with implications for therapeutic interventions.